2008
DOI: 10.1016/j.ultras.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a quarter-wavelength particle concentrator

Abstract: a b s t r a c tA series of devices have been investigated which use acoustic radiation forces to concentrate micron sized particles. These multi-layered resonators use a quarter-wavelength resonance in order to position an acoustic pressure node close to the top surface of a fluid layer such that particles migrate towards this surface. As flow-through devices, it is then possible to collect a concentrate of particulates by drawing off the particle stream and separating it from the clarified fluid and so can op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Bacteria have been processed with some success in batch mode using ultrasound to agglomerate them, 30,31 and a quarter-wavelength acoustic device was used to concentrate 1 μm particles in continuous flow. 32 However, no systems have yet emerged that enable continuous flow-based focusing of bacteria or other sub-micrometer particles at recovery rates above 90%, relevant when handling highly dilute suspensions. This paper presents continuous flow-based sub-micrometer particle focusing using two-dimensional BAW-acoustophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria have been processed with some success in batch mode using ultrasound to agglomerate them, 30,31 and a quarter-wavelength acoustic device was used to concentrate 1 μm particles in continuous flow. 32 However, no systems have yet emerged that enable continuous flow-based focusing of bacteria or other sub-micrometer particles at recovery rates above 90%, relevant when handling highly dilute suspensions. This paper presents continuous flow-based sub-micrometer particle focusing using two-dimensional BAW-acoustophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…52,53 It has been found that at diameters of around 1 μm there is a transition to drag-dominated behaviour for operating frequencies of ~2 MHz. 52,54 For these reasons, few studies have demonstrated acoustofluidic concentration of flowing particles with diameter <2 μm 49,55 (Table I). Antfolk et al recently demonstrated focusing of bacteria using a combination of streaming and a two-dimensional resonance; their paper is not included in Table I, as comparable concentration data was not included; however, impressive performance with polystyrene beads as small as 0.5 µm was shown.…”
Section: Introductionmentioning
confidence: 99%
“…This is possible, either by collecting the concentrated stream and removing excess fluid or by moving the plane of particles directly onto a sensor surface. The 20 former approach, essentially a version of some of the filtration approaches described above, has been developed for biohazard detection by Townsend et al 39 who use a quarter-wavelength system to concentrate 1 micron sized spores close to the reflector surface with this concentrated region then extracted through one of two outlets, and separated from the remain clarified region. Quarter-wavelength systems, although typically less efficient than half-wavelength system, do allow the fluidic system to be simplified; as particles move to the surface the flow only needs to be split into two streams to separate the concentrate from the clarified flow, as opposed to a half- 25 wavelength where three are required to remove the clarified flow from both sides of the concentrate.…”
Section: Sensing and Detectionmentioning
confidence: 99%
“…Townsend et al 39 show that for a typical design a change in the reflector thickness of 5% is sufficient to cause a drop in radiation force of 50%. In addition, lateral effects (from non-ideal resonances that have a lateral variation), can cause the node location to vary between a position in the reflector and a position within the fluid channel making it difficult to push particles uniformly onto the reflector surface.…”
mentioning
confidence: 99%